2022
DOI: 10.3390/ma16010129
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles (Ag-NPs) Using Debregeasia Salicifolia for Biological Applications

Abstract: The synthesis of nanoparticles (NPs) using the green route is environmentally harmonious and cost-effective compared to conventional chemical and physical methods. In this study, the green synthesis of silver NPs was carried out using an extract of Debregeasia salicifolia. The synthesized Ag NPs were characterized by means of different techniques i.e., UV-Vis spectroscopy, FTIR spectroscopy, SEM, and XRD. The XRD pattern exhibited distinctive Bragg’s peaks at (200), (111), (311), and (220). The XRD analysis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a separate study, absorption spectra of AgNPs synthesized from Syzygium jambola indicated a peak at 460 nm(Ghareeb et al 2016). Similarly, Khan et al observed a maximum absorption spectrum of AgNPs synthesized from Debregeasia salicifolia leaf extract at 470 nm(Khan et al 2022). As the concentration of AgNO 3 increased, the SPR peak of the AgNPs became more pronounced, reaching its highest intensity at 50 mM of AgNO 3 .…”
mentioning
confidence: 86%
“…In a separate study, absorption spectra of AgNPs synthesized from Syzygium jambola indicated a peak at 460 nm(Ghareeb et al 2016). Similarly, Khan et al observed a maximum absorption spectrum of AgNPs synthesized from Debregeasia salicifolia leaf extract at 470 nm(Khan et al 2022). As the concentration of AgNO 3 increased, the SPR peak of the AgNPs became more pronounced, reaching its highest intensity at 50 mM of AgNO 3 .…”
mentioning
confidence: 86%
“…Figure a depicts the FT-IR spectrum of the synthesized nanocomposite, which possesses a broad peak between 3568 and 3343 cm –1 possibly due to lattice water or atmospheric water. The band at 2941 cm –1 is due to C–H stretching . The peak at 1595 cm –1 is because of the aromatic CC stretch.…”
Section: Resultsmentioning
confidence: 99%
“…The plates were stored at 37 °C for 24 h, aer which the antibacterial activity was evaluated by measuring the diameter of the inhibitory zone produced by the tested bacteria. 37,38 Field trial and assessment of BioAgNPs…”
Section: Antibacterial Activity Of Bioagnpsmentioning
confidence: 99%